(untitled) (INTERNATIONAL SEMINAR, 2023)
Hoaxes are one of the biggest challenges for parents in educating children amidst the rapid development of technology today. Anti-hoax literacy is one solution in anticipating children accessing and believing hoax information. This research aims to foster an anti-hoax literacy culture with a modern approach to wisdom. The research method uses descriptive qualitative research and related articles as data sources. Data analysis uses reduction, presentation, and conclusion. The research results show that introducing local wisdom, cooperation, respect for ancestral knowledge, deliberation, social ethics, and gardening habits/cooperation traditions form a strong foundation. Through these activities, parents can guide children to understand the cultural context, develop critical thinking skills, and build a responsible attitude in managing digital information. This approach creates anti-hoax solid literacy and helps shape children’s intelligent, collaborative, and resilient characters in this digital era.